Brand Equity Dalam Menghadapi Turbulensi Lingkungan - Maulvi, Herzi Rahmatia; Dida, Susanne; Setianti, Yanti (Jurnal Common, 2022)
Brand is a crucial part in a success of a business. The more well-known and consumed the brand is by people, the higher is its revenue. The success of a brand is often determined by the brand strength. However, despite the great effort by the company to strengthen the brand, sometimes there are unexpected environmental turbulences that no one can control. These turbulences could result in negative impact and potentially threaten the business. In addition, it could also negatively affect the brand position in the market. Based on previous literature study, it is suggested that brand equity can resist environmental turbulences. This article is written using a literature study method from various sources namely books, scientific journals and online-based information. The purpose of this writing is to analyze how brand equity can sustain brand from environmental turbulence. Keywords: Branding, brand equity, environmental turbulence